Optimizing Broiler Production in Urban Area Using Liquid Premix - Apriliana Devi Anggraini; Septi Nur Wulan Mulatmi; Akhis Sholeh Ismail; Lutfi Bayu Sidi Aji; Mochammad Fariz Yovanda (Jurnal Peternakan, 2023)
High temperature in narrow areas  can cause heat stress in broiler. In this condition, broiler performance will decrease, so efforts are needed to deal with these negative impacts. One of them is by  providing premix as a supplement. This study aims to find the best dose of  commercial premix containing vitamins C, E, and  micronutrients to improve the performance of broilers reared in areas with ambient temperatures above thermoneutral. The study  used a total of 160 Cobb strains day old chick (DOC)  with 4 treatments and 5 replications. Each replication consisted of 8 chicks. The treatment  was a premix dose consisting of P0 (0 mL); P1 (0.1 mL); P2 (0.15 mL); and P3 (0.20 mL). The ambient temperature was 29-30 °C and 70% humidity. The  observed data were  the body weight, the average body weight gain, feed consumption,  water consumption intake, and feed conversion ratio (FCR). The data c were analyzed by completely randomized design. Results of this study showed that the use of premix as a feed supplement did not significantly different (P>0.05) on the broiler performance. The average body weight gain at 28 days was 1689 grams, 132 grams of feed intake, 320 mL of drinking intake, and FCR 1.55. The use of premix with dose up to 0.20 mL as a feed supplement for broiler in narrow areas has not shown a significant improvement in performance.